Thermochromic textiles structures: dynamic ambient light design - Cabral, Isabel (2014)
Innovation in the emerging field of smart textiles is providing challenging materials and technologies, which require new knowledge and skills in the design practice. This scenario also represents new possibilities to interact with people and environment. To achieve different ambient light, several lamps or dimmers that regulate the light intensity are normally applied. Focusing on light, the aim of this study is to develop textile structure, printed with thermochromic and conventional pigments, with dynamic behaviour that changes ambient light without acting upon the light source. The developed design process addresses a set of results and conclusions of previous research on how to combine and print with the above-mentioned materials in order to achieve differences in light transmittance when the thermochromic textiles are activated. The product development explores textile expressions and structural possibilities through origami techniques, strengthening and highlighting the effect between morphology and light projections. As a result, designed thermochromic textile structure affect light in colour and intensity outcomes, creating dynamic ambient light.